METHODS OF DEVELOPING STUDENT ACTIVITY THROUGH MODELING PEDAGOGICAL ACTIVITY IN THE EDUCATIONAL PROCESS - Saparbayev Sarvar Soatboyevich; Matchonov Shohrukh Matkarim ogli (International Journal of Literature and Language Studies, 2026)
Modern higher education requires innovative pedagogical approaches that promote active student participation and competency development. Traditional teacher-centered instruction is gradually being replaced by learner-centered methodologies that encourage independent learning, collaboration, creativity, and critical thinking. One of the most effective approaches supporting these educational transformations is pedagogical activity modeling, which enables instructors to systematically design, implement, and evaluate teaching processes. This article examines the theoretical foundations of pedagogical activity modeling and analyzes methods for developing student activity through innovative instructional strategies. Particular attention is given to project-based learning, problem-based learning, collaborative learning, digital technologies, learning management systems, and artificial intelligence. The study concludes that well-designed pedagogical models significantly improve student engagement, motivation, academic achievement, and professional competence while enhancing the overall quality of higher education.